Authenticity and the commodification of heartlands in Singapore. - Hu, Tian Yun. (2011)
Authenticity is a key issue raised in many tourism studies. In this paper, the authenticity of tourist place will be discussed in relation to the broader strategy of place promotion in tourism. In fact, tourism discourses have pointed that tourism will in turn leads to the production of what MacCannell (1973) termed as the‘staged authenticity’ with the process of commodification in tourism. Hence, in this paper, with the use of the case study of Singapore’s ‘Heartlands’, it will be argued that tourism may not lead to the loss of authenticity of a place even with the promotion of the place as tourist destination. In fact, one should consider the extent of commodification of the place in examing the issue of authenticity in tourist place.